Screening for HIV and linkage to care in adolescents: insights from a systematic review of recent interventions in high- versus low- and middle-income settings - Zanoni BC; Elliott RJ; Neilan AM; Haberer JE (Dove Medical Press, 2018)
Brian C Zanoni,1,2 Ryan J Elliott,3 Anne M Neilan,1,2 Jessica E Haberer1,2 1Department of Global Health, Massachusetts General Hospital, Boston, MA, USA; 2Department of Medicine, Harvard Medical School, Boston, MA, USA; 3Premedical Program, Harvard Extension School, Cambridge, MA, USA Introduction: Compared to adults, adolescents and young adults have a higher incidence of HIV infection, yet lower rates of HIV testing. Few evidence-based interventions effectively diagnose new HIV infections among adolescents while successfully providing linkage to care. Methods: We conducted a systematic review of recent interventions to increase HIV testing among adolescents and young adults using data retrieved from PubMed and Google Scholar, and using abstracts presented at the International AIDS Society conferences and Conference on Retroviruses and Opportunistic Infections published between January 1, 2015, and April 28, 2018. Results: We identified 36 interventions (N=14 in high- income countries and N=22 in low- and middle-income countries) that were published in the literature (N=28) or presented at conferences (N=8). Interventions were categorized as behavioral/educational, alternate venue/self-testing, youth-friendly services, technology/mobile health, incentives, or peer-based/community-based interventions. The studies consisted of randomized controlled trials (RCTs), prospective and retrospective observational studies, and quasi-experimental/pre–post evaluations with variable sample sizes. Study designs, populations, and settings varied. All categories showed some degree of acceptability, yet not all interventions were effective in increasing HIV testing. Effectiveness was seen in more than one RCT involving technology/mobile health (2/3 RCTs) and alternative venue/self-testing (3/3 RCTs) interventions, and only in one RCT each for behavioral interventions, community interventions, and incentives. There were no effective RCTs for adolescent-friendly services. Data were limited on the number of new infections identified and on the methods to increase linkage to care after diagnosis. Conclusion: Future studies should include combinations of proven methods for engaging adolescents in HIV testing, while ensuring effective methods of linkage to care. Keywords: adolescent, HIV, testing, interventions, barriers